(untitled) (Altre Modernità, 2019)
The defeat of the twentieth century revolutionary movements leaves a gigantic void. The space of hope can be taken up again by the renewal of the utopian dimension. Utopia must be conceived as a criterion of meaning, as an indication of direction and not as a social model to be realized. Recognizing Marx’s brilliant diagnostic skills but criticizing his erroneous prognosis and his ruinous therapies, we must draw from the critique of the category of fetishism the implications that allow us to understand why global capitalism does not generate a subject capable of becoming aware of its possible overcoming. The very category of politics, as a projection of evil on the adversary, has become useless if one must imagine the current condition of interdependence as capable of evolving towards a pact of balance and peace among peoples, classes, genders, with an eco-friendly use of natural resources. Utopia can be built over a very long period, transforming the level of awareness to experiment projects of evolutionary coexistence.